Carcinoma of the Esophagus in Sulaimany Province - Hawramy, Tahir A.; Golpy, Faiq M. Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2002)
Eighty three 83 patients presented with carcinoma of the esophagus were studied in Sulaimany Teaching Hospital from 1990-1999. The incidence of carcinoma of esophagus among population of Sulaimany province was 6.6Yo of all the malignant tumors, females were more affected than males. Most sufferers were patients from low socioeconomic state and of rural areas of long winter seasons.
Keywords: Caeciuoma of esophagus in Kurdistan incidence arcinoma of esophas female are more affected than